Does learning about race prevent substance abuse? Racial discrimination, racial socialization and substance use among African Americans. (October 2016) - Thompson, Azure B.; Goodman, Melody S.; Kwate, Naa Oyo A.
Highlights: On average, respondents reported experiencing racial discrimination in four settings. Experiencing racial discrimination increased the risk of weekend and problematic alcohol use. Moderation effects of racial socialization on these increased risks were tested. Increased risks of weekend and problematic alcohol use were not moderated by racial socialization.